(3ebOeI aj GdeMGSHI GdeGdjI habG deYGjjQ GdeMGSHI GdeUQjI hGdOhdjIs - (3eMeO YHGS(B, (3HOhjs; (3YHO GdhgGH fUQ Gddg(B, s ((3GdGScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI(B,s)
(3LQO GdCUhd GdKGHJI(B-(3LQO hJShjI GdeNRhf(B-(3LQO hJShjI GdYedGA(B- (3LQO hJShjI ChQGb GdbHV(B- (3LQO hJShjI GdfbOjI(B-(3LQO hJShjI GdNUhe(B- (3GdeMGSHI Yf YedjGJ GdeTQhY GdUfGYj(B- (3hQbI GdYed hGdbhGFe GdeGdjI ddeTQhY GdUfGYj(B- (3GdjhejGJ GdeSGYOI hGdMSGHGJ GdeSGYOI GdGLeGdjI(B- (3GdCNWGA GdeMGSHjI hcjajI eYGdLJgGs
Keywords: (3GdeMGSHIs; (3GdeMGSHI GdOhdjIs; (3eMGSHI GdJcGdjas